Alternative splicing during Arabidopsis flower development results in constitutive and stage-regulated isoforms - Wang, Haifeng; You, Chenjiang; Chang, Fang; Wang, Yingxiang; Wang, Lei; Qi, Ji; Ma, Hong (Frontiers in Genetics, 2014)
Alternative splicing (AS) is a process in eukaryotic gene expression, in which the primary transcript of a multi-exon gene is spliced into two or more different mature transcripts, thereby increasing proteome diversity. AS is often regulated differentially between different tissues or developmental stages. Recent studies suggested that up to 60% of intron-containing genes in Arabidopsis thaliana undergo AS. Yet little is known about this complicated and important process during floral development. To investigate the preferential expression of different isoforms of individual alternatively spliced genes, we used high throughput RNA-Seq technology to explore the transcriptomes of three floral development stages of Arabidopsis thaliana and obtained information of various alternative splicing events. We identified approximately 24,000 genes that were expressed at one or more of these stages, and found that nearly 25% of multi-exon genes had two or more spliced variants. This is less frequent than the previously reported 40%~60% for multiple organs and stages of A. thaliana, indicating that many genes expressed in floral development function with a single predominant isoform. On the other hand, 1,716 isoforms were differentially expressed between the three stages, suggesting that AS might still play important roles in stage transition during floral development. Moreover, 337 novel transcribed regions were identified and most of them have a single exon. In addition, our analyses provide a comprehensive survey of alternative splicing in floral development and facilitate further genomic and genetic studies.